The Influence Of Expository Learning Methods On Mathematics Learning Results For Class III Students : Pengaruh Metode Pembelajaran Ekspositori Terhadap Hasil Belajar Matematika Siswa Kelas III - Claudia Cikita Ade Chintya; Nur Efendi (Universitas Muhammadiyah Sidoarjo, 2021)
Mathematics is a scientific discipline that is abstract and full of problems that must be solved. One of the goals of learning mathematics is to encourage students to become problem solvers by thinking critically, logically, and rationally. To achieve this goal, we need the right learning method, namely the expository learning method. The expository method is a learning method that emphasizes the process of delivering material verbally from a teacher to a group of students with the intention that students can master the subject matter optimally. To test whether the expository learning method really has an effect on mathematics learning outcomes, this study aims to: (1) describe whether the expository learning method has an effect on student learning outcomes, (2) describe how much influence the expository learning method has on student learning outcomes.This research uses quantitative research. The method used is the method of documentation and tests. The subjects in this study were all third grade students of SDN Tambakrejo I Krembung, totaling 32 students. The subjects studied were mathematics with multiplication and division material.The results showed that (1) there was a positive and significant effect of the expository learning method on mathematics learning outcomes as indicated by the value of tcount > ttable or 10.29 > 0.05, and (2) the large influence of the expository learning method on learning outcomes.Thus the results of this study indicate that there is a significant and large influence between the expository learning method on the mathematics learning outcomes of third grade students at SDN Tambakrejo I Krembung. So, students, it is easier to absorb mathematics lessons using the expository method.